Room temperature oxidative desulfurization with MoO3 subnanoclusters supported on MCM-4. Issue 37 (9th July 2019) - Yang, Qianfan; Wang, Jiasheng; Wang, Wan-Hui; Bao, Ming
Abstract : MoO3 subnanoclusters encapsulated in MCM-41 exhibited enhanced catalytic activity and stability for oxidative desulfurization at room temperature. Abstract : Subnano MoO3 /MCM-41 was successfully prepared through doping (NH4 )6 Mo7 O24 in the synthesis process of MCM-41. The morphology of MoO3 /MCM-41 was visually observed by TEM and HADDF-STEM. N2 sorption, XPS and Raman were further applied to investigate the structure of the material. MoO3 /MCM-41 was used in the oxidative desulfurization process with tert -butyl hydroperoxide as oxidant. MoO3 /MCM-41 showed outstanding catalytic activity and recycling ability at room temperature.